PENGOLAHAN LIMBAH AMPAS JAHE INDUSTRI SERBUK JAHE INSTAN DENGAN DESTILASI UNTUK MENGHASILKAN MINYAK ATSIRI - Wati Sukmawati; Hadi Sunaryo (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
UMKM of instant ginger powder has been throwing away ginger dregs from the process of making instant ginger powder. Ginger dregs that have been produced so far are considered as waste that has no economic value and benefits. Based on observations made by the service team, the ginger dregs still smelled like ginger, so it could be concluded that the dregs still contained essential oils. Essential oils are oils contained in several plants such as ginger, nutmeg, lemongrass etc. The essential oil contained in ginger pulp is an export commodity with high economic value because it is widely used for ingredients in the cosmetic, food, aromatherapy and pharmaceutical industries which are adapted to the quality of the oil. The ginger dregs processing method uses steam distillation technique. The ginger dregs are put into a distillation apparatus which is added with water and then heated for 5-6 hours over medium heat. After the ginger dregs mixture evaporates, the water vapor comes out and is accommodated. After the distillation process is complete, the distillate is separated by decantation technique to separate the oil and water layers. In this process, 10 ml of distilled essential oil is produced which can be used for air freshener.